Prevention of VTE in orthopedic surgery patients - Spandonaro, Federico; Mancusi, Rossella Letizia; Terranova, Lorenzo; Giannarelli, Diana; Grossi, Paolo; Imberti, Davide; Mazza, Emilio (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
Venous thromboembolism (VTE) is defined as the obstruction, partial or complete, of one or more veins of deep circulation. It is a condition that can lead to a deterioration in his state of health until death, manifesting as deep vein thrombosis (DVT) or pulmonary embolism (PE). The major orthopedic surgery and the surgical oncology are frequently associated with thromboembolic complications, because of conditions that are often critical in these patients. It is estimated that in Italy DVT has an incidence that varies between 50 and 150 new cases per 100,000 population, while the prevalence would be between 2.5 and 5%. In the absence of thromboprophylaxis, the orthopedic surgery lead to a high increased risk of VTE. In elective hip replacement, in the absence of prophylaxis, the incidence of DVT and of fatal PE is about 50% and 2% respectively. In elective knee arthroplasty the risk of venous thromboembolic complications is even higher. It is estimated that 56.2% of the costs of prophylaxis with Low Molecular Weight Heparin (LMWH) in patients undergoing major orthopedic surgery are attributable to the cost of drugs (about € 200), followed (with 44.8%) by the cost of administration (approximately € 159). The average total cost/day was estimated at € 8 per patient. In Italy, it has been estimated an annual cost for new cases between 215 and 260 million €. The clinical advantages of the New Oral Anticoagulants (NOA) appear to be substantially clear, the major concern with regard to their reimbursement is therefore linked to the financial impact, due to the higher cost per day of the NOA compared with LMWH. To this end, it was built a model of budget impact, in the perspective of the Italian NHS, from the data related to cases of major surgical orthopedic procedures and a meta-analysis on the pivotal RCT, which aims to measure the differential effects in terms of prevention of VTE. The results show that the financial impact of the NOA in the prophylaxis of major orthopedic surgery is not particularly relevant. In fact, the major pharmaceutical costs that, at national level, amount to € 10.8 mil. (€ 15.2 mil. in the case of prolonged prophylaxis in knee operations) would be more than offset by savings in terms of fewer treatments of VTE, which is based on the assumption of more than 4,000 cases, up to about 6,600 in hypothesis best efficacy.